Preparation, Structural Characterization and in Vitro Antioxidant Activity of Selenized Polygonatum sibiricum Polysaccharides - ZHAO Xinyue, WANG Qingyu, WANG Baixuan, ZHAO Qingxu, LI Dapeng, YANG Yue (Shipin Kexue)
Selenized Polygonatum sibiricum polysaccharides (PSP-Se) were prepared using a redox system containing glacial acetic acid and sodium selenite and characterized inductively coupled plasma atomic emission spectrometry (ICP-AES), gas chromatography-mass spectrometry (GC-MS), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), particle size and zeta potential analysis. The antioxidant activity of Polygonatum sibiricum polysaccharides (PSP) and PSP-Se were evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, 2,2’-diazide-bis (3-ethyl-benzothiazole-6-sulfonic acid) (ABTS) cation radical assay and hydroxyl radical assays. The results showed that the optimal conditions for the preparation of PSP-Se were determined by response surface methodology (RSM) as follows: 1.5 g of sodium selenite and 3.0 mL of glacial acetic acid per g of PSP, 80 ℃ and 12 h. The as-prepared PSP-Se contained (6.00 ± 0.20) mg/g of Se, exhibited a spherical morphology with a particle size of 1 654 nm, and showed improved thermal stability and a 95.12% increase in the absolute value of the zeta potential compared with PSP. After selenium modification, the basic skeleton of PSP was preserved. Monosaccharide composition analysis showed that PSP-Se but not PSP contained N-acetyl-glucosamine and N-acetyl-galactosamine, with differences in the contents of shared monosaccharide components being observed between them. FTIR spectroscopy showed that two new absorption peaks appeared at 1 131 and 900 cm-1 in PSP-Se, indicating the formation of selenite ester bonds and successful selenization. In vitro antioxidant assays demonstrated that PSP-Se had significantly higher scavenging capacity against DPPH, ABTS cation and hydroxyl radical compared with PSP (P < 0.05), in a dose-dependent manner.